1987
DOI: 10.1161/01.cir.75.5.914
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cardiopulmonary baroreflex after cardiac transplantation in humans.

Abstract: There is ample evidence for efferent cardiac denervation in patients after cardiac transplantation. However, little is known regarding the effects of the cardiac deafferentation that also results. We examined responses to graded lower-body negative pressure and thus cardiopulmonary baroreceptor unloading in 23 patients 3 to 12 months after cardiac transplantation and compared their responses with those of nine normal subjects. Responses of mean arterial pressure, forearm vascular resistance, and plasma norepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(45 citation statements)
references
References 34 publications
1
43
1
Order By: Relevance
“…19 The normal response of FVR at Ϫ40 mm Hg LBNP in patients with Chagas' disease indicates that when both arterial and cardiopulmonary receptors are unloaded, the reflex control of FVR is preserved. Previous studies with patients with cardiac transplantation 12 and heart failure 20,21 demonstrated a defect on reflex control of FBF and resistance during application of low and high levels of LBNP. In these studies, the reflex modulated by cardiopulmonary receptors was considered compromised, although the arterial baroreceptor reflex might also be simultaneously enrolled.…”
Section: Discussionmentioning
confidence: 91%
“…19 The normal response of FVR at Ϫ40 mm Hg LBNP in patients with Chagas' disease indicates that when both arterial and cardiopulmonary receptors are unloaded, the reflex control of FVR is preserved. Previous studies with patients with cardiac transplantation 12 and heart failure 20,21 demonstrated a defect on reflex control of FBF and resistance during application of low and high levels of LBNP. In these studies, the reflex modulated by cardiopulmonary receptors was considered compromised, although the arterial baroreceptor reflex might also be simultaneously enrolled.…”
Section: Discussionmentioning
confidence: 91%
“…[4][5][6] In contrast, prevention of carotid baroreceptor deactivation during LBNP was found to have no effect on this vasoconstrictor response, supporting the theory that, during orthostatic stress, unloading of cardiopulmonary, not sinoaortic, baroreceptors is the primary mechanism causing reflex vasoconstriction in the peripheral circulation.78 However, recent data from intraneural recordings of muscle sympathetic nerve activity (MSNA) call this theory into question. In normal humans, decreases in ventricular contractility with 8-adrenergic blockade had no effect on the reflex increases in MSNA evoked by decreases in central venous pressure,9 negating one of the principal pieces of evidence linking reflex vasoconstriction to ventricular mechanoreceptor deactivation.…”
mentioning
confidence: 99%
“…14 They also show that this is the case for the forearm vascular and plasma norepinephrine responses to leg raising. This offers additional evidence that cardiac (and also in this instance ventricular) receptors modulate systemic vascular resistance, thereby showing that cardiac receptors are involved not only in blood volume but also in blood pressure control.…”
Section: Reflex Control Of Vasomotor Tonementioning
confidence: 90%